The Brotherhood of Freemason Sisters. Gender, Secrecy, and Fraternity in Italian Masonic Lodges de Lilith Mahmud - de los Reyes Heredia, Guillermo (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2015)
Lilith Mahmud. The Brotherhood of Freemason Sisters: Gender, Secrecy, and Fraternity in Italian Masonic Lodges. Chicago: University of Chicago Press, 2014. 256 pages. ISBN: ISBN: 978-0-226-09586-8